Constraint in Adoption of Neem Coated Urea (NCU) in Madhya Pradesh - Chouhan, R. S.; Niranjan, H. K.; Sharma, H. O.; Rathi, D.; Kurmi, H. S. (International Journal of Bio-resource and Stress Management, 2018)
The study comprising of 400 respondents of two major kharif crops i.e. paddy and soybean of Madhya Pradesh to analyze the adoption behavior, constraints in adoption of NCU fertilizers among selected farmers. More than 60% farmers were found to be aware to NCU and majority of them reported that the main source of awareness was officials of Agriculture Department in Madhya Pradesh. Lack of knowledge about uses of NCU, difficulty in calculating the RDF from different brand of fertilizer available in the market, lake of knowledge about method of application of fertilizer, and lack of awareness about fertilizer use in crop husbandry are the major constraints reported by majority in the area under study. Awareness amongst farmers regarding integrated nutrients management with NCU is required to be created. Packaging/minikit of fertilizer for an acre should be done in such a way so that one bag of fertilizer will serve the purpose of applying recommended doses of fertilizers for different crops as per Agro-Climatic Zones of the state. The farmers are not able to calculate desired nutrients to be applied from the various brands of fertilizers available in the market having different proportion of nutrients. Introduction of national Gateway with respect to e-marketing of seed fertilizer and other inputs at the door step of the farmers to assure quality at reasonable price and timely delivery at desired place.